PROFIL METAKOGNISI SISWA SEKOLAH DASAR DALAM MENYELESAIKAN MASALAH MATEMATIKA DITINJAU DARI GAYA KOGNITIF - Qur Rotul Aini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2018)
The purpose of this study is to describe the metacognitive abilities of elementary school students in the problem in terms of reflective-impulsive cognitive style. This research is a qualitative research with an explorative approach. Subjects in this study were 2 class V students who each had a reflective and impulsive cognitive style. The data integrated in this study are MFFT Test (Macthing Familiar Figure Test), Metacognition Ability Test (MAT) 1 and 2, interview guidelines and measurement. Data analysis techniques using Milles and Huberman models, namely data reduction, data presentation, and conclusion drawing to process validity data using trebulation techniques by taking the same data with different techniques. Based on the results of the study showed that the reflective subject had conducted metacognitive activities that included, monitored, and compared them with indicators in each of the more metacognitive activities fulfilled. While impulsive subjects conduct metacognitive activities which include planning, monitoring and evaluation, but there are still many indicators of each metacognitive activity that has not been fulfilled. It can be concluded that the metacognition profile of the reflective subject is better than the impulsive subject.